Keystone Institutions of Democratic Governance Across Indigenous North America - Holland-Lulewicz, Jacob; Thompson, Victor D.; Birch, Jennifer; Grier, Colin (Frontiers in Political Science, 2022)
Defining and examining democracy in non-Western contexts is a conceptual challenge. This is largely because scholars of contemporary political systems outside of anthropology can envision no alternative pathways other than Western expressions of democracy. Such thinking inhibits our understanding of past, and indeed future, democratic systems. In this paper, we argue that there is no such thing as a “democracy,” but rather there are institutions that facilitate democratic governance. More specifically, we argue that in Indigenous North America “keystone institutions” facilitated complex institutional arrangements and broad participation by a citizenry in the distribution of power and authority. While these characteristics define such Western democratic institutions as the Athenian assembly, the Icelandic Althing, or the U.S. Congress, we argue that comparable keystone institutions of governance can be identified across Indigenous North America. To illustrate these points, we provide a series of cases that demonstrate the variability in the forms that democratic keystone institutions might take. We specifically focus on axes of variability related to the scale and scope of participation facilitated by each institution, the degree to which the institutions distribute power equitably, and the complexity and formality of the institutional arrangements held together by the keystone institution. Importantly, we argue that the concept of the keystone institution as an analytical tool for seeking out the emergence and role of democratic forms of governance transcends the utility of dichotomous categories such as Western/non-Western or state/non-state that limit productive comparative frameworks and the inclusion of non-traditional case studies of democracy in global conversations.